Athletes using ergogenic and medical sport supplements report more favourable attitudes to doping than non-users. Issue 3 (March 2021) - Hurst, Philip; Ring, Christopher; Kavussanu, Maria
Abstract: Objectives: Our study objectives were twofold: 1) examine whether users and non-users of different types of sport supplements vary in doping attitudes and sport supplement beliefs, and 2) determine whether the type of sport supplement is directly and indirectly (via sport supplement beliefs) related to doping attitudes. Design: Cross-sectional survey. Methods: Athletes (N = 557; 77% male, mean ± standard deviation; age = 20.8 ± 4.5 years, training = 5.7 ± 4.2 h per week, competing = 11.1 ± 5.2 years) completed measures of sport supplement use, sport supplement beliefs, and doping attitudes. Sport supplements were classified into: ergogenic, medical, sport food and drinks, and superfoods. Results: Compared to non-users, users of ergogenic ( d = 0.31, p < 0.01) and medical ( d = 0.42, p < 0.01) sport supplements reported more favourable attitudes towards doping. In addition, compared to non-users, users of ergogenic ( d = 1.10, p < 0.01), medical ( d = 0.80, p < 0.01) and sport food/drink ( d = 0.58, p < 0.01) supplements reported stronger beliefs in the effectiveness of sport supplements to improve sport performance. Use of ergogenic, medical and sport food/drink supplements was indirectly related to doping attitudes via sport supplement beliefs. Conclusions: Researchers examining the relationship between sport supplement use and doping should differentiate between sport supplement types to improve measurement accuracy. Sport practitioners administering ergogenic and medical sport supplements to athletes may need to provide additional anti-doping education to counteract any favourable attitudes towards doping.